Entropy Principle for the Development of Complex Biotic Systems : Organisms, Ecosystems, the Earth. - Aoki, Ichiro (Elsevier insights., 2012)
The concept of entropy in thermodynamics is a complex one, though it is fundamental in understanding physics, the workings of the mind, and biology. Entropy is the measure of the quality of energy, and it can also refer to the turn from order to disorder or randomness in isolated systems. In open systems, such as biology, entropy is formulated in terms of production and energy flow. This book establishes a novel view of complex biological systems and the earth using this concept of entropy, encompassing the interdisciplinary area of biology, ecology and physics. This book considers the development over time of a range of biologically complex systems such as plants, animals, humans, and ecosystems, describing them in terms of the second law of thermodynamics, entropy. With its broad coverage of biological systems, this book will be useful for students of environmental science as well as students in biology and physics.